Uncommon paleodistribution patterns of Chrysolophus pheasants in east Asia: explanations and implications. (20th April 2015) - Lyu, Nan; Päckert, Martin; Tietze, Dieter Thomas; Sun, Yue‐Hua
Abstract : Some modeling studies indicated that the past distributions of species in east Asia during the Last Interglacial (LIG) and Last Glacial Maximum (LGM) periods differ from those of European and North American species and the deviant Asian distribution pattern is known under the term 'pre‐LGM expansion'. It represents the unusually similar distribution patterns between the current and the LGM scenario. However, there is still no satisfying explanation for this phenomenon so far. Therefore, we took the two recently separated pheasant species of genus Chrysolophus in east Asia as an example to test the pattern by performing ecological niche models. The main findings of this study include: 1) the paleodistributions of these two pheasants also corresponded to the 'pre‐LGM expansion' pattern; 2) climatic similarity results from mobility‐oriented parity analysis also revealed similar pattern for both species; 3) climate regimes of east Asia showed patterns different from those in Europe and North America in a climate shift towards drier conditions and stronger seasonality and to more extreme temperatures of the coldest months particularly during the LIG; 4) the two Chrysolophus species occupied significantly different ecological niches according to current distribution. We suggest that ecological segregation established in allopatric glacial refugia should be the main determinants for the separation of two Chrysolophus species until they came into extant post‐Pleistocene contact.